Perencanaan Pengembangan Usaha Kreatif Tenun Ikat (Studi Usaha Kreatif di Desa Manulondo Kabupaten Ende) - Rodja, Yakobus Alfons (Jurnal Ilmiah Administrasi Publik, 2018)
The development planning of creative bind-weaving business (creative business study in Manulondo Village of Ende Regency) aims to improve the welfare and financial revenue of the region which will impact on the increase of local revenue (PAD) of Ende Regency. The focus of this research is based on the planning theory according to Tjokroamidjojo (1995) which defines planning as a thorough and continuous process of activities of planning, implementation, monitoring and evaluation. By using interactive data analysis method, the result of research obtained is that planning of business development of creative sub-sector of bindweaving has not run optimally. This is due to the lack of clarity of the intentions contained in the public policy and human resources apparatus that has not been adequate